Keluarga Sakinah: Analisis Tafsir Klasik dan Fikih Modern atas Qs. Ar-Rum: 21 - Rum, Muhammad; Sholiha, Hidayatus (Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
The high divorce rate in Indonesia,reaching 394,608 cases in 2024,signals a persistent gap between the ideals of Islamic family life and the realities of contemporary Muslim marital practice. This study conducts a comparative analysis of the concepts of sakinah, mawaddah, and rahmah in QS. Ar-Rum: 21 through two complementary epistemological frameworks: (1) classical Qur'anic interpretation employing riwayah-based (At-Tabari) and dirayah-based (Ar-Razi) methodologies, and (2) modern contextual jurisprudence (Al-Qaradawi, Wahbah Zuhaily, Al-Munajjid). Using a library research approach within a textual-interpretivist paradigm, the study finds that the divergent hermeneutical paradigms of At-Tabari and Ar-Razi yield epistemologically distinct yet complementary contributions: At-Tabari foregrounds fitrah and sunnatullah, while Ar-Razi foregrounds theological-philosophical dimensions. Modern jurists converge on the view that all three concepts must be operationalized through sincere communication, responsible leadership, and spiritual awareness. The theoretical contribution of this study lies in constructing an integrative three-pillar model (sakinah-mawaddah-rahmah) with practical indicators, bridging classical tafsir epistemology and modern jurisprudential operationalization. This model offers a concrete framework for pre-marital guidance programs, family counseling, and Muslim family resilience policies in Indonesia.